Photo-functionalized TiO2 film for facile immobilization of EpCAM antibodies and efficient enrichment of circulating tumor cells - Deng, Huan; Liu, Xiangqin; Chen, Jie; He, Yi; Lin, Lanke; Liu, Xin; Chen, Jiang; Liu, Xiaoqi (Frontiers in Pharmacology, 2023)
The highly efficient capture of circulating tumor cells (CTCs) in the blood is essential for the screening, treatment, and assessment of the risk of metastasis or recurrence of cancer. Immobilizing specific antibodies, such as EpCAM antibodies, on the material’s surface is currently the primary method for efficiently capturing CTCs. However, the strategies for immobilizing antibodies usually have the disadvantages of requiring multiple chemical reagents and a complex pre-treatment process. Herein we developed a simple strategy for the immobilization of EpCAM antibodies without additional chemical reagents. By utilizing the positive charge property of the photo-functionalized titanium dioxide (TiO2), the negatively charged carboxyl terminal of EpCAM antibodies was immobilized by electrostatic interaction, allowing the antibodies to expose the antigen binding site fully. The experimental results showed that the photo-functionalized TiO2 surface had a marked positive charge and super-hydrophilic properties that could immobilize large amounts of EpCAM antibodies and keep excellent activity. CTCs capture experiments in vitro showed that the EpCAM antibodies-modified photo-functionalized TiO2 could efficiently capture CTCs. The results of blood circulation experiments in rabbits showed that the EpCAM antibodies-modified photo-functionalized TiO2 could accurately capture CTCs from the whole body’s blood. It was foreseen that the strategy of simple immobilization of EpCAM antibodies based on photo-functionalized TiO2 is expected to serve in the efficient capture of CTCs in the future.